2021
DOI: 10.1016/j.nmni.2021.100867
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of arrhythmias in COVID-19 patients, a study in the Shahid Mostafa Khomeini Hospital of Ilam from March to August 2020

Abstract: Introduction Cardiac arrhythmias are important causes of death among populations and always responsible for a high percentage of mortality in hospitalized patients. The aim of this study was to evaluate the frequency of arrhythmias in COVID-19 patients in the Shahid Mostafa Khomeini Hospital of Ilam from March to August 2020. Materials and Methods In this descriptive-analytical study, all the COVID-19 patients with a cardiac condition admitted to the intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Recently, a patient with protracted COVID-19 infection that presented with chest pain, palpitations and shortness of breath was found to have PVC bigeminy and elimination of these with catheter ablation resulted in successful clinical outcomes [ 93 ]. In a prospective analysis performed in Shahid Mostafa Khomeini Hospital of Ilam in Iran from March to August, 2020, it was revealed that A-Fib and PVC (20%) are the most common arrhythmias followed by VT (4.44%) and VF (2.22%) [ 94 ]. In a worldwide retrospective analysis of hospitalized COVID-19 patients, atrial fibrillation, NSVT, VT and VF occurred in 62%, 9.2%, 8.2% and 4% of these cases, respectively [ 95 ].…”
Section: Main Textmentioning
confidence: 99%
“…Recently, a patient with protracted COVID-19 infection that presented with chest pain, palpitations and shortness of breath was found to have PVC bigeminy and elimination of these with catheter ablation resulted in successful clinical outcomes [ 93 ]. In a prospective analysis performed in Shahid Mostafa Khomeini Hospital of Ilam in Iran from March to August, 2020, it was revealed that A-Fib and PVC (20%) are the most common arrhythmias followed by VT (4.44%) and VF (2.22%) [ 94 ]. In a worldwide retrospective analysis of hospitalized COVID-19 patients, atrial fibrillation, NSVT, VT and VF occurred in 62%, 9.2%, 8.2% and 4% of these cases, respectively [ 95 ].…”
Section: Main Textmentioning
confidence: 99%
“…Although arrhythmias are uncommon in COVID-19 patients, they can be lethal which can be prevented by prompt recognition [4]. Premature ventricular contractions (PVCs) are a type of arrhythmia described as premature heart contractions and early depolarization of the myocardium originating in one of both ventricles due to an electrical impulse or ectopic rhythm from any part of the ventricles before the sinoatrial impulse has reached the ventricles [5].…”
Section: Introductionmentioning
confidence: 99%